Optimasi Kinerja Sistem Operasi Berbasis Linux untuk Aplikasi IoT - Rayhan Praditya Saruji; Daviqho Suaditya; Aidil Ikhsan; Indra Gunawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Optimizing the performance of Linux-based operating systems for IoT applications in the trading sector is an important strategy in improving operational efficiency and competitiveness. This study explores Linux optimization techniques that can be applied to IoT systems to improve the speed, stability, and security of applications in the trading environment. This research method is carried out using descriptive qualitative through interviews, literature studies and observations. This study focuses on resource management and the implementation of advanced security features. Case studies on several real implementations show that by applying optimization techniques, such as process priority settings and routine updates, system performance can be significantly improved. The results of the study show that proper optimization can reduce system latency, increase data output, and strengthen security, which ultimately supports the success of IoT applications in the trading sector.